CALML5 is a novel diagnostic marker for differentiating thymic squamous cell carcinoma from type B3 thymoma. Issue 12 (16th March 2023) - Kanamori, Koichiro; Suina, Kentaro; Shukuya, Takehito; Takahashi, Fumiyuki; Hayashi, Takuo; Hara, Kieko; Saito, Tsuyoshi; Mitsuishi, Yoichiro; Shimamura, Shoko Sonobe; Winardi, Wira; Tajima, Ken; Ko, Ryo; et al.
Abstract: Background: Thymic squamous cell carcinoma and type B3 thymoma are primary neoplasms of the anterior mediastinum that are sometimes difficult to differentiate from one another histologically. However, only a few immunohistochemical markers are available for the differential diagnosis. The purpose of this study was to discover a novel marker for differentiating between thymic squamous cell carcinoma and type B3 thymoma. Methods: We used histological samples of thymic carcinomas ( n = 26) and type B3 thymomas ( n = 38) which were resected between 1986 and 2017. To search for candidates of differential markers, gene expression levels were evaluated in samples using promoter analysis by cap analysis of gene expression (CAGE) sequencing. Results: Promoter level expression of CALML5 genes was significantly higher in thymic carcinomas than in type B3 thymomas. We further validated the results of the CAGE analysis in all 26 thymic carcinomas and 38 type B3 thymomas by immunohistochemistry (IHC). CALML5 was strongly expressed in the cytoplasm in 19 of 26 cases with thymic carcinoma, whereas positivity at the protein level was shown in two of 38 type B3 thymomas. Thus, the sensitivity (73.1%) and specificity (94.7%) of CALML5 as markers for immunohistochemical diagnosis of thymic carcinoma were extremely high. Conclusion: We identified CALML5 as a potential marker for differentiating thymic squamous cell carcinoma from type B3 thymoma. It is assumed that future clinical use of CALML5 may improve the diagnostic accuracy of differentiating between these two diseases. Abstract : Type B3 thymoma, the most malignant type of thymoma, is associated with cytological atypia, making its differentiation from thymic carcinoma difficult. CD5, c‐kit, and GLUT‐1 have been used as markers for differentiating thymic carcinoma from thymoma, although their sensitivity and specificity are not sufficient. We performed cap analysis of gene expression (CAGE) sequencing and immunohistochemistry (IHC) using histological samples of thymic carcinomas ( n = 26) and type B3 thymomas ( n = 38) which were surgically resected. CALML5 was identified as a potential marker for differentiating thymic squamous cell carcinoma from type B3 thymoma.